Theology In The Classroom: How Tensions Help Teachers Reform Their Ideas On Education - Bram de Muynck (STTRII, 2021)
Christian teachers do not naturally connect theology with their professional practice. This article explores the reasons for this, which all have to do with how theory functions in teaching. Theory will mainly come into focus when practical problems arise, but theological concepts are not the first to come into view. The article states that tensions that teachers experience in practice are triggers for theological reflection. This is in coherence with the call for Christians to test and discern what is the will of God (Rom. 12:2). Teachers are supposed to be able to reflect on three dimensions where tensions can be recognized. The first is the response to general cultural ideas. The second is the call for a collective theological vision in school teams. Finally, existential tensions find solutions in theological language. Prospective Christian teachers should have training in to reflect on those three levels.